Land, Church, Forced Removals and Community on Klipfontein Farm in the District of Alexandria, Eastern Cape c. 1872 - 1979 - Bezuidenhout, GJW (Rhodes University, Faculty of Humanities, Department of History, 2017)
This thesis is a case study of how church, land and dispossession of land has influenced identity formation of a coloured community in the Eastern Province, namely the Klipfontein community. Coloured history in the Eastern Province has largely been neglected. This study attempts to rectify such a lack of in-depth enquiry as it may lead to misinterpretations that may influence contemporary politics and identity formation. Through research based on primary sources, it is evident that the social landscape of Klipfontein Farm and the relationships between that community and surrounding black African and white communities have largely been shaped by the stipulations contained in the joint will of the community's ancestors: Dirk and Sarah Janse van Rensburg. The land devolved into a trust and has been administered by trustees since the death of the first spouse in 1877. By keeping the land in a trust, it enabled the descendants to continue to live on the farm in perpetuity, without the risk of being forced off the land via financial restraints or racially-based legislation. But the usufructuaries could also never fully utilise Klipfontein as an agricultural concern due to a combination of a lack of equipment and skill, and the provisions of the will. These complications inevitably led to inter-familial disputes and tension. Before 1939 there had already been three court cases dealing with the interpretations of the Will. In that same year the Supreme Court ordered that tracts of the land, including a part of Boesmansriviermond village, be sold in order to pay off arrear rates and taxes. Although the responsibility for these sales lay with the trustees, the community has been suspicious of the usufructuaries ever since. A key element of the Klipfontein identity is their religion. The church legitimises their right to the farm - against those who wish to take that right away. Their claim to occupation is couched in scriptural discourse, viewing Klipfontein as 'their Garden of Eden' that God gave to the stamvader, Dirk Janse van Rensburg. This seemed to have been partially successful for the Klipfontein community in staving off harassment by authorities. It also caused friction between the community and the black African residents. Some usufructuaries and family members felt that such right was exclusively given to the coloured community and so they became increasingly annoyed by the black Africans who settled there. Other usufructuaries did not share this feeling. They allowed evicted black African farm labourers to settle on certain portions of Klipfontein until the late 1970s. The black African population rapidly increased due to misinformation and evictions from neighbouring farms. This only further exacerbated the inter-familial conflict between usufructuaries, flaring tensions between the black Africans and their reluctant hosts as well as animosity from the white community towards Klipfontein. In 1979, after a series of court cases, a decision was made to remove all the African settlers by force and relocate most of them to the 'homeland' of Ciskei. The rest, who were of 'working-age' were left behind in a 'temporary emergency camp' on the outskirts of Kenton-on-Sea. The effects of these removals still impact the relationships between the different racial groups in the area to this day.
Keywords: Janse van Rensburg family; Klipfontein Farm (Alexandria, -- South Africa); Alexandria (South Africa) -- History; Colored people (South Africa) -- History; Colored people (South Africa) -- Religion; Colored people (South Africa) -- Relocation; Black people -- Relocation -- South Africa -- Eastern Cape; Family farms -- South Africa -- Eastern Cape; Church history -- South Africa -- Eastern Cape; Land tenure -- Law and legilstion -- South Africa; Land reform -- Law and legislation -- South Africa